Filtration materials and filters for retaining polycyclic aromatic hydrocarbons, carbonyls and other compounds derived from smoke from tobacco products

Hybrid filtration materials using activated carbon and graphene-based nanomaterials on a porous polymer matrix address the challenge of selective smoke filtration, enhancing health benefits while preserving taste and aroma in tobacco products.

JP7602765B2Active Publication Date: 2024-12-19CO IND DE TABACOS MONTE PAZ SA
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2021560437
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-10
Filing Date
2020-03-03
Publication Date
2024-12-19
Estimated Expiration
2040-03-03

AI Technical Summary

Technical Problem

Existing filtration technologies for cigarette smoke fail to selectively remove undesirable health compounds while preserving the sensory properties of tobacco products, leading to indiscriminate filtration that affects taste and aroma.

Method used

Development of hybrid filtration materials comprising activated carbon and graphene-based nanomaterials supported on a porous polymer matrix, which are integrated into a single compartment filter to achieve high selectivity for polycyclic aromatic hydrocarbons and carbonyls.

Benefits of technology

The hybrid materials effectively reduce undesirable compounds in cigarette smoke while maintaining the taste and aroma, providing a balanced health and commercial value for tobacco products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602765000005
    Figure 0007602765000005
  • Figure 0007602765000006
    Figure 0007602765000006
  • Figure 0007602765000007
    Figure 0007602765000007
Patent Text Reader

Abstract

The present invention relates to a hybrid graphene material and a filter capable of retaining, in whole or in part, polycyclic aromatic hydrocarbons, carbonyls, and other compounds derived from tobacco products or smoke from industrial processes. The filter has activated carbon and graphene material as adsorbent materials, both supported by the same matrix and located in the same compartment of the filter, and this compartment is optionally connected to another compartment of a conventional filter containing fibers of cellulose acetate or similar polymers. The present invention also relates to a method for producing the hybrid graphene material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is in the field of filtration systems and materials, more specifically in the field of a hybrid filter preparation process based mainly on micro- and nano-carbon materials supported on a porous polymer structure.

[0002] In particular, but not exclusively, in the field of gas filters which simultaneously exhibit particular selectivity for polycyclic aromatic hydrocarbons, such as those present in the primary smoke stream of tobacco products, and high selectivity for carbonyls and other smoke compounds. [Background technology]

[0003] Cigarette smoke is divided into the primary stream that enters the smoker's body, the sidestream or "secondary smoke", which is a mixture of smoke exhaled by the smoker and smoke from the sidestream of the cigarette, and "third-hand smoke", or environmental pollution that persists even after the tobacco product has been extinguished. The particles and vapor fractions in cigarette smoke contain thousands of chemicals distributed according to the graph shown in Figure 1. Among these are groups or families of chemicals that are particularly undesirable because of their toxicity. Undesirable health compounds or families are often referred to as Hoffman compounds or families, which are grouped according to their chemical structure and functionality.

[0004] Indiscriminate filtration to eliminate or reduce the levels of these substances will also eliminate substances that, while not toxic, contribute to the taste and aroma of the cigarette, thus affecting its organoleptic properties and thus its commercial value.

[0005] For this reason, in order to harmonize the commercial and health requirements of tobacco products, technologies that allow the selective extraction to reduce or eliminate undesirable products from smoke, improving its health profile but respecting its sensory properties, have become particularly important.

[0006] The interest in selective filters and their presence on the market is not new; a typical example is the "Dalmatian" filter, activated carbon particles on cellulose acetate fibers, which has been known for several decades.

[0007] It has long been demonstrated that coal exhibits selectivity towards carbonyls and, to bear the coal on a highly porous polymeric support, it makes it possible to obtain filters with a high concentration of carbon material and thus achieve better results.

[0008] In recent years, there has been an increasing interest in the development and research of graphene-based porous nanomaterials, since they combine the properties of graphene materials with a pore structure that provides these materials with a large specific surface area. This makes them excellent candidates for the manufacture of various types of filtration systems due to their potential commercial applications and interesting physicochemical properties related to their ability to retain various types of molecules, especially organic molecules. This ability therefore opens up many potential applications in the development of highly efficient filtration systems.

[0009] The activated carbon / binder polymer system (polyethylene of very high molecular weight) has already been developed by Celanese Acetate (CelFx Technology), whose novelty is due to the high concentration of activated carbon encapsulated in a highly porous carrier. After the trade agreement with Celanese, the co-owners have exploited this development in the Floyd cigarette brand in various versions. Patent document 1 suggests the possibility of investigating the use of this porous material as a carrier for a myriad of possible materials and chemicals, including new forms of carbon such as graphene, nanotubes, fullerenes, etc., but in practice so far this has not been applied in any market product. This document describes a porous material filter with high molecular weight active particles and plasticizers, with the porous material wound around the longitudinal axis, and optionally with activated carbon and graphene, in separate sections of the same filter. The filter described in this document therefore does not correspond to the filter of interest of the present invention.

[0010] US Pat. No. 5,399,433, which claims priority from Chinese patent US Pat. No. 5,399,433, describes graphene-based filters that differ from those of the present invention in two main aspects. The materials described are not hybrid materials, and the graphene they refer to, graphene aerogel, is pure graphene. This aspect makes the present invention very difficult to implement due to the cost of conventional cigarettes. Another difference is that the types of filters described in this document are segmented, while those of the present invention are unique cavity filters.

[0011] US Patent No. 5,399,633 refers to a material with filtering capabilities in which graphene is adsorbed onto cellulose fibers. This material differs from the material of the present invention in that the graphene present in the claimed hybrid material is adsorbed onto fine particles of activated carbon, and these particles are incorporated into a highly porous polymer matrix. This makes the process of obtaining the hybrid material more scalable and economically feasible.

[0012] Other Chinese patents, US Pat. No. 5,399,413, US Pat. No. 5,499,521, US Pat. No. 5,599,633, and US Pat. No. 5,599,643, refer to filters of various cavities or portions, one of which is made of graphene or graphene oxide alone or supported on cellulose acetate, however, none of them describes the use of hybrid graphene materials, methods for obtaining graphene, or the use of exfoliated graphene in surfactant-assisted aqueous media, as described in the present invention.

[0013] US Patent No. 5,399,663 describes a method for the synthesis of graphene and a reusable filter based thereon, which may be a separate item or may be attached to a cigarette. The object of the invention of US Patent No. 5,399,663 is quite different from that claimed in the present invention, since it does not use hybrid graphene materials, the synthesis method is different from the method used in the present invention, and the type of filter proposed is different from that of the present invention.

[0014] US Pat. No. 5,399,633 refers to the use of carbon nanotubes scattered on a substrate in a filter to reduce and / or eliminate the number of constituents in a fluid, which may be water or air.

[0015] The above mentioned documents do not consider the use of a multicomponent composite material based on activated carbon and graphene materials supported on a polymer matrix in the same compartment, nor do they implement a matrix that supports the graphene and makes it possible to produce a viable filter as in the present invention.

[0016] In summary, none of the documents disclosed herein reveals a technical solution of how to incorporate carbon nanomaterials into a highly porous polymer matrix that allows the production of a filter with an appropriate pressure drop according to the intended application (e.g. for the production of a tobacco smoke filter).

[0017] It is (arguably) particularly relevant that no consideration is given to the use of graphene or graphene materials and activated carbon in the same compartment, as described in the present invention, which would be a major technical advantage in terms of filter manufacturing and cost-effectiveness. [Prior art documents] [Patent documents]

[0018] [Patent Document 1] WO2012 / 054111 [Patent Document 2] CN2017 / 071331 [Patent Document 3] US2019 / 0000136 A1 [Patent Document 4] CN105054291(A) [Patent Document 5] CN204444223 [Patent Document 6] CN204444224 [Patent Document 7] CN108378416A [Patent Document 8] CN107373750 [Patent Document 9] WO2017 / 187453 [Patent Document 10] WO2010 / 126686 Summary of the Invention

[0019] [Summary of the invention] In general, the present invention relates to deactivated and / or activated micro- and nano-carbon materials, such as graphene, graphene oxide, few layer graphene sheets, carbon nanotubes, graphite and carbon nanoparticles obtained from pure graphite supported on activated carbon, and contained on a porous polymer matrix, which are particularly suitable for use in the manufacture of gas (in particular, but not exclusively) filters.

[0020] The present invention also includes the development of methods for preparing hybrid materials such as: micronized graphite / activated carbon / activated or deactivated nanocarbon material / highly porous polymer, particularly suitable for use in the manufacture of filtration systems.

[0021] Furthermore, the present invention relates to the design and development of a filter with high selectivity and efficiency for volatile compounds in general, and carbonyls and aromatic and polycyclic aromatic hydrocarbons in particular, made from the hybrid material of the subject invention, which is particularly suitable, but not limited to, for the manufacture of smoke filters for tobacco products, although this material may also be used in water and gas filters manufactured by industries other than tobacco.

[0022] [Detailed Description of the Invention] The present invention consists of the development of hybrid materials based on graphene oxide, and / or graphene, and / or few layer graphene sheets, and / or carbon nanotubes, supported on particles of activated carbon and / or micronized graphite (fully or partially activated), thus acting as a microstructural support for nanocarbon materials. These hybrid particles have a highly porous micro- and nanoscale architecture, as well as a high degree of adhesion to nanocarbon materials. 2 It is homogeneously incorporated into highly porous polymer supports to obtain macroscopic hybrid systems that exhibit very high specific surface areas of >100 nm / g.

[0023] Meanwhile, the present invention discloses a method to obtain this hybrid material, as well as the design and development of a highly selective and efficient filter for filtering tobacco smoke in cigarettes, generally but not limited to volatile compounds.

[0024] [Materials covered by this invention] So-called hybrid or composite materials consist of two or more materials with different physicochemical properties which, when combined, result in another material with properties other than those of the individual components.

[0025] "Nanocarbon materials" are carbon-based nanomaterials such as fullerenes, nanotubes, nanofibers, graphene, graphene oxide, few-layer graphene sheets, and exfoliated graphite, and have become one of the most important material families in the last decade due to their unique physical, chemical, and mechanical properties.

[0026] Among the nanocarbon materials used in the present invention are carbon nanotubes. Carbon nanotubes are structures in which graphene planes are rolled up to form tubes with open or closed ends. There are two types of nanotubes: multi-walled nanotubes (MWNTs), which are the most readily available, and single-walled nanotubes (SWNTs). MWNTs are essentially constructed by multiple radii of SWNTs located concentrically with one another. With regard to their mechanical properties, all evidence indicates that nanotubes are very flexible and resistant to breaking, stretching and compression. Nanotubes have a relatively large thermal stability (they start to degrade at 750°C in air and about 2800°C in vacuum) and are estimated to have a thermal conductivity twice that of diamond. Nanotubes have a mass of 1.33-1.44 g / cm 3 300 m for single-walled nanotubes, which is important for the present invention, and due to their structure and physical morphology, they have a large surface area (approximately 1000 m for single-walled nanotubes). 2 / g).

[0027] "Graphene oxide" may be incorporated into the claimed material. Graphene oxide is a graphene material of interest in itself and is also one of the main precursors of graphene. Its atomic structure is characterized by the hybridization sp 2It consists of a single layer of carbon atoms with carbon hexagons having a structure of 0.01 to 0.01 mm, but unlike graphene, a certain percentage of these are randomly bonded to oxygen atoms, forming a hybridization sp 3 Thus, the surface of graphene oxide is functionalized on both sides with hydroxyl, epoxide and carbonyl groups, and the edges are functionalized with carboxyl groups. Various types of molecules can be attached to graphene oxide by both covalent and non-covalent bonds.

[0028] Another nanomaterial that is incorporated into the hybrid material is graphene. The crystal structure of graphene is sp 2 It consists of a two-dimensional array of honeycomb-shaped carbon atoms covalently linked to each other by bonds, making it the first example of the actual existence of a two-dimensional crystal. The thickness of a single layer of graphene ranges from 0.34 nm to 1.6 nm. In the case of graphene, its reactivity is mainly due to non-covalent interactions, since ideally no oxygenated functional groups should be exhibited in its structure. Despite the above, in practice, this process leads to a certain percentage of residual oxo groups, so that they can also be established, albeit to a small extent, from covalent bonds with organic molecules.

[0029] During the process of obtaining the hybrid materials disclosed herein, a mixture of graphene and "few-layer graphene sheets" is obtained. Few-layer graphene sheets (few-layer graphene) are obtained by stacking 3 to 10 graphene sheets.

[0030] In particular, the huge system of π-delocalized electrons that characterize graphene systems provides an electron-rich sheet structure on both sides, which results in a strong affinity for aromatic compounds, thus making them excellent adsorbents for aromatic compounds.

[0031] The material disclosed in this invention is defined as a hybrid graphene material with previously unreported properties, and has shown superior performance when used in the manufacture of cigarette filters.

[0032] [Hybrid material collection process] The hybrid material process described above (Figure 2) basically consists of a first step of micronization of graphite or carbon material by applying ultrasound to an aqueous dispersion of this material. The use of commercially available graphite is useful for this process. In this process, surfactants or stabilizers such as polysorbates, polyvinylpyrrolidone, N-methylpyrrolidone, sodium dodecyl sulfate, etc., may or may not be incorporated into the aqueous solution at appropriate concentrations.

[0033] The two embodiments may be used to produce nano-carbon materials, or Graphene oxide may be obtained by one of the usual methods, for example by the modified Hummer method or by liquid phase exfoliation assisted by the presence of surfactants and / or stabilizers as described above in a medium using high performance rotor-stator type equipment.

[0034] In a typical synthesis of graphene oxide, 2 g of graphite is weighed out and to this is added 100 ml of concentrated H2SO4 with stirring in a shaker plate at room temperature. The mixture is placed in an ice bath until the ice bath temperature drops to about 5°C, and about 8 g of KMnO4 is added to the mixture by magnetic stirring and ice bath. 100 ml of cold distilled water is added very slowly. This is left stirring for 1.5 hours. H2O2 is added drop by drop until the mixture stops bubbling. The mixture is left to stand overnight. The supernatant is discarded. Washing is performed by centrifugation or by decanting the solution. The pellet is washed with 5% HCl in successive steps until the pH reaches a value close to or above 3. It is sonicated with a pointer sonicator to obtain exfoliated graphene oxide.

[0035] The graphene oxide thus obtained can be used as it is and / or as reduced graphene oxide. To achieve this reduction, different methods can be used, such as chemical, thermal or hydrothermal reduction. Graphene oxide was obtained using a hydrothermal reactor. The exfoliated graphene oxide suspension is placed into the autoclave until a filling rate in the range of 70-80% of the total autoclave volume is reached and heated to a temperature in the range of 100-130 °C for 4-12 hours.

[0036] The synthesis of few-layer graphene is carried out in surfactant-assisted liquid phase using a high-energy pointer sonicator or by high-performance stator-rotor type instruments.

[0037] A typical synthesis involves the treatment of 10 g of graphite suspended in a volume ranging from 200 to 1000 ml. The surfactant used is dissolved in this solution in a percentage ranging from 1 to 20%. Micronization of the graphite used as precursor in the above synthesis can also be achieved by aqueous phase sonication.

[0038] The above forms the nanocarbon material that is later used to produce hybrid materials: Graphene oxide, graphene, few layer graphene sheets, exfoliated graphene, carbon nanoparticles or carbon nanotubes are provided.

[0039] The activation process is a process that creates pores in the carbon material. This activation process can determine the micro- and nanostructure of the resulting material (defects, pores, edges, layer size) and therefore dramatically affect its performance as a molecular filter.

[0040] Various methods can be used to activate the carbon material, such as oxidative treatment in the presence of strong acids such as sulfuric and nitric acids, solid state treatment of the carbon precursor with sodium or potassium hydroxide at elevated temperatures, or, preferably, treatment with gases such as nitrogen or carbon dioxide or mixtures thereof at elevated temperatures.

[0041] Activation of the obtained graphene materials is preferably carried out in the gas phase, for which purpose these dry materials are subjected to, for example, a hot CO2 flow in a closed oven within a temperature range of 500-1100 °C for a period of 1-10 hours.

[0042] The graphene material thus obtained is mixed with activated carbon, for example of a particle size distribution of 35-70 mesh, under stirring, for example at a temperature in the range of 50-90° C. for a period long enough to keep the suspension temporarily stable. After this period, the system is subjected to vacuum evaporation, for example at a temperature in the range of 50-70° C., to obtain a dry carbon material, which is then combined with high molecular weight polyethylene.

[0043] The present invention also includes the development of composite materials made from the above hybrid materials incorporating metal salts, particularly copper, zinc and iron, supported on highly porous polymeric supports.

[0044] The present invention also includes the development of composite materials made from the above hybrid materials and metal nanoparticles such as copper, zinc and iron supported on highly porous polymeric supports.

[0045] The present invention also includes the development of composite materials made from the above hybrid materials and particulate zeolites substituted with metals such as copper, iron or zinc supported on highly porous polymeric supports.

[0046] [Filter design and development] With respect to the filtration system that is the subject of the present invention, a filter material has been developed in which graphene and activated carbon are simultaneously immobilized on a porous material made of very high molecular weight polyethylene, which has the advantage of forming a compound structure that binds to the sorbent particles, resulting in a filter with almost no resistance to the passage of smoke and a very low pressure drop.

[0047] In the systems of complexity we consider, the predominantly non-polar and predominantly sp 2There are indeed many types of molecular interactions that are conditioned by hybridization. In general, such interactions are usually covered by the concept of dispersion forces (van der Waals, London, Debye, Keeshon, etc.).

[0048] In our case, activated carbon is a disordered form of graphite with a random or amorphous structure, but at the atomic scale, local structures of aromatic rings exist beneath the morphology of randomly oriented graphene nanocrystals. (1) Considering the interaction of the σ-π orbital set between the aromatic rings of graphene and the graphene nanocrystals of activated carbon (Hunter and Sanders (2,3) ) are of particular importance. These interactions are outlined in Figure 3 and appear with different strengths depending on the mutual orientation of the interacting systems. Given the greatest stabilizing force of the σ-π bonds, π-π repulsions are overcome.

[0049] In the filtration system covered by this patent, these nanocarbon combinations are mixed with high molecular weight polyethylene and subjected to a temperature of 200°C for 20 minutes to obtain a highly porous material carrying the adsorbent particles. This is a typical sintering process, in which a thermoplastic material is heated to a high temperature but below its melting temperature to form strong bonds between its particles by atomic diffusion at the contact points between those particles.

[0050] This sintering process may be carried out on a mould, which in the case of cigarette filters may be a cylinder of a diameter suited to the design of the cigarette in which it is intended to be fitted. This operation may also be carried out continuously on a device specially designed for such purpose.

[0051] In Figure 4, a SEM (Scanning Electron Microscope) image of a very high molecular weight polyethylene sintered porous material can be seen. In Figure 5, a SEM image of a filter body of the invention is shown, where the sintered particles (distinct color) forming a support structure between the carbon particles can be seen.

[0052] The invention involved the study of the balance between the particle size distributions of the components (nanometer and meter) and the investigation of the most appropriate mixing procedure to avoid mutually damaging interactions between the adsorption capacities of the adsorbents involved.

[0053] This study showed that no such negative interactions existed and the filter operated efficiently for retention of polycyclic aromatic hydrocarbons, carbonyls and volatile compounds. The proportions of the filter components were also adjusted to produce a porous material of optimal physical properties, especially with regard to hardness, porosity and filter capacity.

[0054] The filter of the invention also has the advantage of achieving successful filtration of two large groups of undesirable cigarette smoke constituents in a single filter sector, and can be applied to various tobacco products such as cigarettes, pipes, hookahs, e-cigarettes, products that heat but do not burn tobacco (HNB, "non-combustion heating"), and any other smoke or vapor releasing device. In the particular case of commercial application to the design of cigarettes, another sector made of cellulose acetate fibers following the traditional structure of conventional filter cigarettes is attached to this sector. This second sector provides some non-selective filtering effects, but its main purpose in our case is to incorporate a clean termination at the mouth end of the cigarette, and finally, in the designer's opinion, to include a ventilation system by microlaser perforation in the cigarette nozzle, to introduce aroma releasing capsules by manual compression, and even to intervene in the regulation of the residence time of the smoke in contact with the filter material.

[0055] [References] (1) Jeremy C. Palmer, Keith E. Gubbins, Microporous and Mesoporous Materials 154 (2012) 24-27 (2) CA Hunter, JKM Sanders, J. Am. Chem. Soc. 1980, 112, 5525-3534 (3) Ch. R. Martinez, BL Iverson, Chem. Sci. 2012, 3, 2191 [Brief description of the drawings]

[0056] [Figure 1] FIG. 1 is a diagram (pie chart) illustrating the chemical composition of cigarette smoke. [Diagram 2] FIG. 1 shows a scheme illustrating the different stages for obtaining the subject material of the present invention. [Diagram 3] FIG. 1 shows a scheme of the interaction of a set of σ-π orbitals between the aromatic rings of graphene and the graphene nanocrystals of activated carbon. [Figure 4] FIG. 1 shows a SEM (scanning electron microscope) image of a porous material synthesized from very high molecular weight polyethylene, where the porous structure can be observed. [Diagram 5] FIG. 1 shows an SEM image of a filter of the present invention, in which the synthesized particles and distinct color tones are observed, forming support structures between the carbon particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0057] [Examples of filter efficiencies disclosed in this patent (application)]

[0058] [Case 1] Cigarettes A and B were analyzed according to the overall design of the illustration below.

[0059] [ka]

[0060] The composition of the porous mass of these cigarettes is as follows: Cigarette A: Activated carbon 70% + graphene 6% + GUR 24% Cigarette B: Activated carbon 70% + GUR 30% (reference example)

[0061] The main difference between the two cigarettes is the presence of graphene in the porous material of A. Other physical and chemical properties are very similar for both products, and the nozzle aeration is 60% in both cases. The pressure drop was maintained in the range of 120-140 mmH2O. The tobacco in both tobacco columns is the same.

[0062] The two groups of cigarettes were smoked simultaneously in a Cerulean SM450 smoking machine under the Health Canada Intensive regimen (six replicates of each cigarette) and the extracts were analyzed according to an internal method for quantifying 13 polycyclic aromatic hydrocarbons. The results of the analysis are summarized in Table I and show a significant reduction in several polycyclic aromatic hydrocarbons in the smoke of the main cigarette stream for Cigarette B (reference example).

[0063] [Table 1]

[0064] [Case 2] Cigarette C, whose design corresponds to that of Case 1, was analyzed in comparison with the reference cigarette 1R6F from the University of Kentucky, which is an international standard cigarette for research work and serves as a basis for comparing data from different laboratories. Cigarette C has a sector that includes a porous material having the following composition: Cigarette C: Activated carbon 71% + graphene 11% + GUR 18% Incidentally, cigarette 1R6F is a cigarette equipped with a conventional cellulose acetate filter.

[0065] Both cigarettes were smoked simultaneously in a Cerulean SM450 smoking machine using the Health Canada Intensive method (six replicates of each cigarette). The results of the analysis are summarized in Table II, which makes it possible to compare the polycyclic aromatic hydrocarbon reduction capabilities of several of the filters under this patent (application).

[0066] [Table 2]

[0067] [Case 3] In the smoke of cigarette C of case 2, the carbonyl reduction was evaluated by comparing it with the results obtained for the reference cigarette 1R6F. Two cigarettes were smoked using the ISO 3308:2012 method and the extracts were analyzed according to CRM74:2018 for the determination of the eight carbonyls (six replicates for each cigarette). The results are summarized in Table III and allow the comparison of the carbonyl reduction capacity of the filters according to this patent (application).

[0068] [Table 3]

Claims

1. The nanocarbon material includes micronized graphite, activated carbon, and one or more of graphene oxide, graphene, and few-layer graphene sheets; The microparticulated graphite, activated carbon and one or more nanocarbon materials are combined with a porous polyethylene support and are 2 / g or more specific surface area, A hybrid carbonaceous material characterized by:

2. A filter capable of retaining polycyclic aromatic hydrocarbons, carbonyl compounds and other compounds in the smoke of a tobacco product, as described below, comprising:

1. A filter comprising one or more nanocarbon materials associated with micronized graphite and activated carbon supported by a porous polyethylene support as specified in claim 1, in the same section of the filter, which section may be attached to another filter section made of cellulose acetate fibers, The filter is capable of reducing the content of the following polycyclic aromatic hydrocarbons in a gas stream by the amounts specified below, as compared to the University of Kentucky International Reference Cigarette 1R6F: naphthalene (93%), acenaphthylene (74%), acenaphthene (73%), fluorene (68%), anthracene (63%), phenanthrene (54%), fluoranthene (52%), pyrene (52%), chrysene (49%), benzo[a]anthracene (45%), benzo[k]fluoranthene (34%), benzo[b]fluoranthene (34%), benzo[a]pyrene (53%), The filter also reduces the following carbonyl compounds by the following percentages, compared to the University of Kentucky International Reference Cigarette 1R6F: formaldehyde (72%), acetaldehyde (82%), acetone (87%), acrolein (89%), propionaldehyde (82%), crotonaldehyde (88%), methyl ethyl ketone (85%), butanal (85%), A filter characterized in that:

3. 2. A method for preparing the hybrid carbonaceous material of claim 1, comprising the steps of: a) micronization of commercial graphite by applying ultrasound to an aqueous dispersion of the commercial graphite; b) After the micronization step a), there are two ways: the modified Hummer method, or Exfoliation of graphite in the liquid phase using high power rotor-stator type equipment, assisted by the presence of surfactants and / or stabilizers in an aqueous medium; A step of synthesizing nanocarbon materials, mainly graphene, few-layer graphene sheets, and / or exfoliated graphene, by c) supporting the nanocarbon material synthesized in step b) on fine particles of activated carbon, while mixing the nanocarbon material with activated carbon by stirring in the suspension at a temperature in the range of 50° C. to 90° C. until the suspension is temporarily stable; d1) evaporating the suspension temporarily stabilized in step c) under vacuum at a temperature ranging from 50° C. to 70° C. to obtain a dried carbon material comprising micronized graphite, activated carbon and nanocarbon material; d2) mixing the dried carbon material obtained in step d1) with high molecular weight polyethylene; The method according to claim 1, further comprising:

4. The method according to claim 3, wherein a surfactant and / or stabilizer is added to the aqueous dispersion in the micronization step a), and the surfactant and / or stabilizer is at least one selected from the group consisting of polysorbate, polyvinylpyrrolidone, N-methylpyrrolidone, and sodium dodecyl sulfate.

5. A filter for a tobacco product having a first compartment and a second compartment, 13. A method for producing a hybrid carbonaceous material according to claim 1 in said first section and cellulose acetate fibers in said second section; A filter capable of retaining at least polycyclic aromatic hydrocarbons and carbonyl compounds in the smoke of a tobacco product.

Citation Information

Patent Citations

  • Graphene composite cigarette filter tip and cigarette with same

    CN105054291A

  • Graphene composite type filter-tipped cigarette

    CN107373750A

  • Three-stage inserting composite multi-position intercepting filter tip

    CN108378416A

  • CN2017/071331

  • Concentric groove cigarette filter stick containing graphene oxide

    CN204444223U